1994
DOI: 10.1111/j.1526-4610.1994.hed3404187.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Neck Pain: The Warning Symptoms of Vertebral Artery Dissection

Abstract: The clinical features of headache and neck pain in 14 patients with extracranial vertebral artery dissection proven by angiography or magnetic resonance imaging are reported. Pain was always located on the side of the dissected vertebral artery. Whereas eleven patients had head and posterior neck pain, the others had either only posterior neck pain, no change of a chronic pre-existing headache or no pain at all. Pain started suddenly, was of sharp quality and severe intensity, different from any previously exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 21 publications
1
59
0
6
Order By: Relevance
“…This agrees with previous studies [4][5][6][7][8]. In ICAD patients, pain was significantly more frequent in the anterior part of the head, compared to VAD, where pain occurred in the nuchal and/or occipital region.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with previous studies [4][5][6][7][8]. In ICAD patients, pain was significantly more frequent in the anterior part of the head, compared to VAD, where pain occurred in the nuchal and/or occipital region.…”
Section: Discussionsupporting
confidence: 92%
“…Headache, facial or neck pain are common presenting symptoms of SCAD, although mechanisms underlying dissection-related pain remains incompletely understood [4][5][6][7][8]. The relationship between previous migraine and painful SCAD was investigated in only two studies with opposite findings and therefore it is still a matter of controversy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The following data were collected from the medical records of the 31 patients: age and sex, clinical symptoms at onset, headache and/or neck pain, 22 clinical diagnosis including subarachnoid hemorrhage, 2,7 possible dissection-related trauma at onset, type of onset, and clinical course.…”
Section: Methodsmentioning
confidence: 99%
“…However, the patient is treated with an analgesic and observed for a period of time when neurological and hematological examinations are negative in cases presenting with sudden severe headache with nausea or vomiting alone, particularly after excluding cerebral or subarachnoid hemorrhage by brain CT and cerebrospinal fluid examination. In fact, the presence of headache alone without symptomssuggestive of cerebral infarction is inadequate for the diagnosis of intracranial dissecting aneurysm and only a few studies have reported the opposite (5,6). In the present patient, severe headache occurred suddenly, such symptomsthat causes subarachnoid hemorrhage were doubted, without clear symptomsof cerebral infarction or subarachnoid hemorrhage.…”
Section: Case Reportmentioning
confidence: 69%
“…While intracranial dissecting aneurysms underlie less than 1 %of unselected brain ischemic events, they mayaccount for 5%or more of ischemic stroke in young adults without risk factors for cerebrovascular disorders (5). Furthermore, most cases (about 89%) have clinical complications such as cerebral infarction or subarachnoid hemorrhage, however 88% of the patients with intracranial dissecting aneurysm make a good recovery (6,7). Development of a sudden severe headache in the occipital region warrants a complete work-up to exclude dissecting aneurysm of the basilar or vertebral artery, including cerebral angiography (2, 3).…”
Section: Case Reportmentioning
confidence: 99%